E-Book Physiotherapy Exercise Methods for Myogenic Low Back Pain - Wanti Hasmar; Faridah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Myogenic low back pain is pain related to stress or strain on the back muscles, tendons and ligaments which are usually present when you do excessive daily activities. Low back pain needs to get attention because it can become a problem such as lost work time, reducing work productivity. Prevention of myogenic low back pain can be in the form of health education to batik artisans using exercise control sheet media. This research is a quasi-experimental study with a one group pre-test post-test design. The sample in this study amounted to 30 people. The sampling technique is by means of proportional stratified random sampling. The results showed that after doing the static stretching exercise, William Flexion Exercise, core stability using a control sheet had not made positive changes for batik craftsmen who experienced myogenic lower back pain.